Coupling Between the Responses of Plants, Soil, and Microorganisms Following Grazing Exclusion in an Overgrazed Grassland - Wang, Zhen; Li, Xiliang; Ji, Baoming; Struik, Paul C.; Jin, Ke; Tang, Shiming (Frontiers in Plant Science, 2021)
Grazing exclusion is an effective management practice to restore grassland ecosystem functioning. However, little is known about the role of soil microbial communities in regulating grassland ecosystem functioning during long-term ecosystem restorations. We evaluated the recovery of a degraded semiarid grassland ecosystem in northern China by investigating plant and soil characteristics and the role of soil microbial communities in ecosystem functioning after 22 years of grazing exclusion. Grazing exclusion significantly increased the alpha diversity and changed the community structure of bacteria, but did not significantly affect the alpha diversity or community structure of fungi. The higher abundance of copiotrophic Proteobacteria and Bacteroidetes with grazing exclusion was due to the higher carbon and nutrient concentrations in the soil, whereas the high abundance of Acidobacteria in overgrazed soils was likely an adaptation to the poor environmental conditions. Bacteria of the Sphingomonadaceae family were associated with C cycling under grazing exclusion. Bacteria of the Nitrospiraceae family, and especially of the Nitrospira genus, played an important role in changes to the N cycle under long-term exclusion of grazing. Quantitative PCR further revealed that grazing exclusion significantly increased the abundance of nitrogen fixing bacteria (nifH), ammonia oxidizers (AOA and AOB), and denitrifying bacteria (nirK and nosZ1). Denitrifying enzyme activity (DEA) was positively correlated with abundance of denitrifying bacteria. The increase in DEA under grazing exclusion suggests that the dependence of DEA on the availability of NO3- produced is due to the combined activity of ammonia oxidizers and denitrifiers. Our findings indicate that decades-long grazing exclusion can trigger changes in the soil bacterial diversity and composition, thus modulating the restoration of grassland ecosystem functions, carbon sequestration and soil fertility.